Exploration of the feasibility of clinical application of phage treatment for multidrug-resistant Serratia marcescens-induced pulmonary infection - Xiangke Duan; Wenfeng Liu; Yanyu Xiao; Man Rao; Liyin Ji; Xiaofu Wan; Shuhong Han; Zixun Lin; Haichen Liu; Peifen Chen; Kun Qiao; Mingbin Zheng; et al. (Emerging Microbes and Infections)
Serratia marcescens (S. marcescens) commonly induces refractory infection due to its multidrug-resistant nature. To date, there have been no reports on the application of phage treatment for S. marcescens infection. This study was conducted to explore the feasibility of phage application in treating refractory S. marcescens infection by collaborating with a 59-year-old male patient with a pulmonary infection of multidrug-resistant S. marcescens. Our experiments included three domains: i) selection of the appropriate phage, ii) verification of the efficacy and safety of the selected phage, iii) confirmation of phage-bacteria interactions. Our results showed that phage Spe5P4 is appropriate for S. marcescens infection. Treatment with phage Spe5P4 showed good efficacy, manifested as amelioration of symptoms, hydrothorax examinations, and chest computed tomography findings. Phage treatment did not worsen hepatic and renal function, immunity-related indices, or indices of routine blood examination. It did not induce or deteriorate drug resistance of the involved antibiotics. Importantly, no adverse events were reported during the treatment or follow-up periods. Thus, phage treatment showed satisfactory safety. Finally, we found that phage treatment did not increase the bacterial load, cytotoxicity, virulence, or phage resistance of S. marcescens, indicating satisfactory phage-bacteria interactions between Spe5P4 and S. marcescens, which are useful for the future application of phage Spe5P4 against S. marcescens. This work provides evidence and a working basis for further application of phage Spe5P4 in treating refractory S. marcescens infections. We also provided a methodological basis for investigating clinical application of phage treatment against multidrug-resistant bacterial infections in the future.